Knowledge and awareness of magnetic resonance imaging safety among healthcare workers in a single medical centre - Mohd Khalil, Rubiah; Zakaria, Faikah; Janudin, Shahrani (Faculty of Medicine, 2026)
Magnetic resonance imaging (MRI)-related incidents reported to the U.S. Food and Drug Administration (FDA) between 2008 and 2017 indicated that 59% involved serious thermal injuries, followed by 11% traumatic events, 9% projectile-related accidents, and 6% acoustic injuries. Locally, a medical centre in Klang Valley recorded three projectile-related MRI incidents between 2015 and 2023 that involved both clinical and non-clinical staff. Despite these occurrences, no official study in Malaysia has assessed healthcare workers’ knowledge and awareness of MRI safety protocols. Given their critical role in ensuring a safe MRI environment, this study aimed to evaluate the level of MRI safety knowledge and awareness among healthcare workers at a single medical centre.